USING THE POTENTIAL OF A TOY BOOK IN THE PREPARATION OF BACHELOR STUDENTS IN THE FIELD OF MATHEMATICAL EDUCATION OF PRESCHOOL CHILDREN - Alekseeva, Tatiana; Mikhailova, Irina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article outlines the problem of using the potential of toy books in preparing bachelor students for purposeful work on the formation of mathematical concepts in preschool children and suggests the idea of organizing the creative activity of students to design toy books with mathematical content.The article contains an overview of classifications of toy books, pedagogically characterized and methodically described examples-constructs of various types of toy books created by bachelor students. The pedagogical potential of these constructs allows us in this work to consider a toy book as a means of mathematical education for preschool children.The purpose of the study is a theoretical description and empirical understanding of the advantages of using the potential of a toy book with mathematical content in the educational activities of a university for the development of creative thinking of future preschool teachers. To achieve the goal, the following methods were used: theoretical analysis of literary sources, Internet resources, analysis of statistical data and a pedagogical experiment.The results of the study showed difficulties in mastering the method of designing a toy book with mathematical content, revealed the preferences of future educators-educators in choosing one or another type of toy book that dominates in its content a mathematical topic and methodological features of its implementation in the presented design form.The conducted research and analysis of the results allowed us to obtain data on the importance of including in the process of training future teachers-educators a creative technique - the design of toy books with mathematical content.